Effect of Particle Size on the Optical Properties of Yellow Silicate Phosphor in Light-Emitting Diodes - Jang, Min-Suk; Kim, Wan-Ho; Kang, Young-Rae; Song, Sang-Bin; Kim, Jae-Pil; Kim, Jin-Hyeok (International journal of applied ceramic technology, 2013)
Understanding the effect of particle size on the optical properties of phosphor is important to increase packaging efficiency in white light‐emitting diodes (LEDs). We have investigated the effect of particle size (10–20 μm, 20–25 μm, 25–32 μm) on the optical properties of a yellow silicate phosphor adopted in white LEDs. X‐ray diffraction results show negligible modification in crystallinity as the particle size of the yellow silicate phosphor varies, whereas the photoluminescence excitation intensity and quantum yield are enhanced as the particle size increased. LED packages fabricated using phosphors with different mean particle sizes, and their optical properties were analyzed. The radiant flux improved with increasing particle size, whereas the luminous flux increased with decreasing particle size. The effect of immersion on the optical properties of the LED light source has been also measured, and the details are discussed.